PRONOSTIC FOETO-MATERNEL DE LA CESARIENNE A L’HOPITAL GENERAL DE REFERENCE INERA YANGAMBI - LYANDE, Ley BAFENO; ATCHALEMA, Franck TOKANEKE; ELIDE , Paulin EWAYA; KAMUNYONGE , Jean Pierre MOKILI; KUMIELE, Paul MANGASA; MOSONGO , Pascal LOKOKOLA; FALANGA , Joséphine MBOKA; TUMBAKO, Madeleine ESABE; NDUYALEGE, Césarine LIBATE; ALUALASO, Jeannette KOMBOZI; MATALA, Gabriel SONGE (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
A child’s birth is a happy event in the hearthstone. But this happening can not drop by myself in the statuses suited. This assertion remains a truth not only for his time but also for our days. This, he is so that the cesarean operation is made often in precarious fortunes and a last urgency to rescue the life of the mother and the child’s these increasingly. This intervention very in the most favorable situation, is associated of a higher hazard of mortality and unwholesomeness at the mom and child by the report of the delivery by a low lane. The cesarean inhabits an important plaza in the obstetric application in our service. Someone make the recourse of this chaque dealings-faith that the delivery-par watches from natural impossible avere. In this vancancy, the actors relate an average frequency of the abdominal delivery in our mass medium of 10,1%, the episodes of age affected by the abdominal delivery are 18-22 years and 28-32 years with 26,7% of case every one followed from it settled over for lowest age to 18 years with 24%, the last parities are refered a lotto with 32% in primipares 29,3% ot in multiprried and 25,4% ot tall multiparried. The majority of the cesarean were earned on the pregnancy of the term, it is 85,3% of these the main indications of the cesarean in our report are the agony foeta the acute with 18,6% ot dystocie aggressive with 18,6% and mechanical dystocie with 16%. Aboard this work on 75 cases of a cesarean done, the actor relate 4% of maternal deaths and 25,3% of complications.